Service quality : customers' expectations and perceptions - a case study of Prego. - Yeo, Irene. (2008)
This research is based on Prego -- a restaurant under the management of the Westin Stamford and Westin Plaza. In this study, 212 diners were asked about their expectations of Prego and their perceived performance of it after the meal. This was carried out in the form of a questionnaire survey. The respondents were also asked to allocate scores to a set of given service quality dimensions -- tangibles, reliability, responsiveness, assurance, empathy and communication.